Iron transformations during low temperature alteration of variably serpentinized rocks from the Samail ophiolite, Oman. (1st February 2018) - Mayhew, Lisa E.; Ellison, Eric T.; Miller, Hannah M.; Kelemen, Peter B.; Templeton, Alexis S.
Abstract: Partially serpentinized peridotites in the Samail ophiolite in the Sultanate of Oman currently undergo low temperature alteration and hydration both at shallow levels, with water recently in contact with the atmosphere, and at depth, with anoxic, reducing fluids. However, it is unclear how changes in the distribution and oxidation state of Fe are driving the production of energy-rich gases such as hydrogen and methane detected in peridotite catchments. We track the Fe transformations in a suite of outcrop samples representing a subset of the spectrum of least to most altered end-members of the Oman peridotites. We use microscale mineralogical and geochemical analyses including QEMSCAN, Raman spectroscopy, synchrotron radiation X-ray fluorescence (XRF) mapping, and electron microprobe wavelength dispersive spectroscopy. The less-altered peridotites possess a diversity of Fe-bearing phases including relict primary minerals (e.g. olivine, pyroxene, chromite) and secondary phases (e.g. serpentine and brucite). Raman spectroscopy and electron microprobe data (Si/(Mg + Fe)) indicate that much of the serpentine is significantly intergrown with brucite on the sub-micron scale. These data also indicate that the Fe content of the brucite ranges from 10 to 20 wt% FeO. The mineral assemblage of the highly reacted rocks is less diverse, dominated by serpentine and carbonate while olivine and brucite are absent. Magnetite is relatively rare and mainly associated with chromite. Goethite and hematite, both Fe(III)-hydroxides, were also identified in the highly altered rocks. Whole rock chemical analyses reflect these mineralogical differences and show that Fe in the partially serpentinized samples is on average more reduced (∼0.40–0.55 Fe 3+ /FeTotal ) than Fe in the highly reacted rocks (∼0.85–0.90 Fe 3+ /FeTotal ). We propose that olivine, brucite, chromite and, perhaps, serpentine in the less-altered peridotites act as reactive phases during low temperature alteration of the Oman peridotite. The pervasive oxidation of Fe(II) in the less-altered peridotites to Fe(III) in the most-altered peridotites during water-rock reaction in the subsurface of the Samail ophiolite may produce H2 which will influence the development of microbial energy sources and habitats, and carbon cycling and sequestration within the (ultra)mafic ocean crust.